2018
DOI: 10.1016/j.cognition.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

The sentence wrap-up dogma

Abstract: Current sentence processing research has focused on early effects of the on-line incremental processes that are performed at each word or constituent during processing. However, less attention has been devoted to what happens at the end of the clause or sentence. More specifically, over the last decade and a half, a lot of effort has been put into avoiding measuring event-related brain potentials (ERPs) at the final word of a sentence, because of the possible effects of sentence wrap-up. This article reviews t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 98 publications
(175 reference statements)
0
48
0
Order By: Relevance
“…All sentences were of the same structure as in Figure 1b: Dass der Fisch groß/klein ist, findet Lara (The fish is big/small, thinks Lara). Therefore, the congruency between the sentence and the prime video becomes only apparent at the critical adjective, and that the critical words do not occur at the sentence‐final position (Stowe, Kaan, Sabourin, & Taylor, 2018). We controlled word length and frequency (Wortschatz Leipzig) at the position of the critical words between both congruency conditions.…”
Section: Methodsmentioning
confidence: 99%
“…All sentences were of the same structure as in Figure 1b: Dass der Fisch groß/klein ist, findet Lara (The fish is big/small, thinks Lara). Therefore, the congruency between the sentence and the prime video becomes only apparent at the critical adjective, and that the critical words do not occur at the sentence‐final position (Stowe, Kaan, Sabourin, & Taylor, 2018). We controlled word length and frequency (Wortschatz Leipzig) at the position of the critical words between both congruency conditions.…”
Section: Methodsmentioning
confidence: 99%
“…However, the second comparison did not yield any significant differences. It is possible that this null result was caused, in part, by sentence 'wrap-up' effects (Hagoort et al, 2003), given that the critical stimuli appeared in sentence-final position, even though recent findings cast doubt on this interpretation (e.g., Stowe et al, 2018). Nevertheless, the authors acknowledged this limitation and suggested that the inclusion of an adverbial or prepositional phrase at the end of the experimental sentences may help resolve the ambiguity of these results.…”
Section: Electrophysiological Measuresmentioning
confidence: 98%
“…All sentences were of the same structure as in Figure 1B: Dass der Fisch groß/klein ist, findet Lara (The fish is big/small, thinks Lara). Therefore, the congruency between the sentence and the prime video becomes only apparent at the critical adjective, and that the critical words do not occur at the sentence-final position (Stowe et al, 2018). We controlled word length and frequency (Wortschatz Leipzig) at the position of the critical words between both congruency conditions.…”
Section: Materials and Proceduresmentioning
confidence: 99%